Does Make Career Plan Important: Empirical Study based on Human Capital Theory - Misna Ariani (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
This research is an analysis of human resources that aims to determine whether theory of human capital (education spending) affects career planning of labor in the mining sector. Using sample of workers in the mining sector was obtained from National Labor Force Survey (SAKERNAS), which had been collected by Central Bureau of Statistics (BPS) in 2010 in the province of East Kalimantan. The samples were 747 formal sector workers. Analysis tools used are Multinomial Logit. The results showed that vocational education and sex had positive significant impact on the workers who work in the mining sector, therefore career planning can be started early in the planning of education (human capital theory). This study is associated with the empirical study if it can be said that the social (education) affect the initial step in a career workforce. Higher education in this study received less opportunity, while vocational education is more likely able to work in the formal sector. Keywords: Education, Gender, Formal Mining Sector